2022
DOI: 10.3390/agriculture12020206
|View full text |Cite
|
Sign up to set email alerts
|

The Eco-Efficiency of Castor Supply Chain: A Greek Case Study

Abstract: Castor is a candidate crop that grows in marginal lands in the Mediterranean area. It can be grown by utilizing minimal resources to provide unique industrial chemicals or to serve as an energy crop. However, it can be also cultivated with intensive inputs providing higher yields. Whether a high input or a low input scheme is more sustainable depends on the economic and environmental impacts of each case. The objective of the present study, therefore, was to evaluate these impacts under the Mediterranean clima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Regarding the effect of nitrogen fertilization, there was an increase in castor seed yield in the treatment supplied with 120 kg N ha −1 , as also reported by Pari et al (2022), who obtained similar results for castor hybrids under a Mediterranean climate with high‐input field management (100 kg N ha −1 ) and Calcagno et al (2023), who investigated the perennial habit of castor under different irrigation and nitrogen fertilization levels in the Mediterranean area while maintaining the crop over a 2‐year period. Weiss (2000) reported that nitrogen fertilization had little effect on seed oil content, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the effect of nitrogen fertilization, there was an increase in castor seed yield in the treatment supplied with 120 kg N ha −1 , as also reported by Pari et al (2022), who obtained similar results for castor hybrids under a Mediterranean climate with high‐input field management (100 kg N ha −1 ) and Calcagno et al (2023), who investigated the perennial habit of castor under different irrigation and nitrogen fertilization levels in the Mediterranean area while maintaining the crop over a 2‐year period. Weiss (2000) reported that nitrogen fertilization had little effect on seed oil content, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 84%
“…Featuring high biodegradability and environmentally friendly characteristics, castor oil has emerged as valid alternative to petroleum-based reagents for the manufacturing of different polymers, including polyurethanes, epoxies, polyamides, and polyesters [1][2][3][4][5]. Compared with other vegetable oils such as soybean oil, rapeseed oil, palm oil, cottonseed oil, or Karanja oil, castor oil has more green characteristics since it does not affect the food chain and it can be grown in marginal lands [6,7]. Furthermore, castor oil is the only commercially available natural oil containing hydroxyl groups (in the ricinoleic acid chains), which have recently attracted particular interest for the preparation of polyurethanes (PUs) [8,9].…”
Section: Introductionmentioning
confidence: 99%